Professional Training of Preschool Education to individual work with children - Куземко, Леся (Educological discourse, 2013)
The importance of the individual approach in a work with preschool children is underscored in the researches of known psychologists, teachers of the past and the present. For successful realization of the individual approach in a work with children, kindergarten teachers should master the appropriate knowledge and skills.